Revitalization of Amsterdam Fort as a Historical Museum and Preservation of Maluku’s Cultural Heritage - Sholeh Hadri; Yudha Kartika; Siti Wardiningsih (CV. Publikasi Indonesia, 2026)
Amsterdam Fort is a historical cultural heritage building located in Hila Village, Central Maluku Regency, Maluku Province, Indonesia. As a colonial heritage with significant historical, architectural, and cultural value, this fort possesses substantial potential for development as an educational facility and historical tourism destination. However, its current utilization remains suboptimal, necessitating revitalization efforts. This research aims to formulate a revitalization concept for Amsterdam Fort as a History Museum and Center for the Preservation of Maluku Cultural Heritage by applying conservation architecture and contextual architecture approaches. The research employed a qualitative-descriptive method with an adaptive reuse strategy. Data collection techniques include field observations, photographic documentation, structured interviews, and literature studies. Data analysis encompasses site, climate, circulation, noise, vegetation, and functional activity analyses. The findings reveal that the revitalization concept successfully integrates historical preservation with contemporary functions through spatial zoning, separated circulation systems, utilization of sea views, and application of local materials adaptive to tropical coastal climates. Conservation and contextual approaches effectively maintain building authenticity while presenting supporting facilities harmonious with the historical character. This revitalization is expected to restore Amsterdam Fort's role as an educational centre, cultural preservation hub, research facility, and historical tourism destination that increases public awareness of cultural heritage preservation and strengthens Maluku's cultural identity. Furthermore, this revitalization contributes to sustainable tourism development and local economic growth. This research provides practical implications as design recommendations for local governments and cultural heritage agencies, as well as theoretical contributions to developing revitalization models based on conservation architecture and contextual approaches.